Organ Transplantation of the Future: Promises and Constraints of Xenotransplantation (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Xenotransplantation from genetically modified animals to humans holds the promise of revolutionise transplantation medicine, addressing the chronic shortage of human organs. Despite the extraordinary results achieved in recent years, many scientific still remain, both scientifically and from an ethical-regulatory point of view. In particular, this paper focuses on the issue of animal testing in the field of xenotransplantation research and, more specifically, on the contradictions between the Italian legislation (Legislative Decree no. 26/2013) and the European Directive 2010/63/EU, which risk hampering scientific and medical progress.
Keywords: Xenotransplantation; genetically modified animals; biotech organs; animal testing; shortage of human organs